Foundations of Nanomechanics from Solid-State Theory to Device Applications - Cleland (Andrew N) (2005)
Nanomechanics ; Solid State Theory
38663a.jpg;38663b.jpg;38663c.jpg;38663d.jpg;38663e.jpg;38663f.jpg
22.5
Keywords: Nanomechanics ; Solid State Theory